Reactions of plant copper/topaquinone amine oxidases with N6-aminoalkyl derivatives of adenine - Lamplot, Zbynĕk; Sebela, Marek; Frycák, Petr; Longu, Silvia; Padiglia, Alessandra; Medda, Rosaria; Floris, Giovanni; Pec, Pavel (Journal of enzyme inhibition and medicinal chemistry, 2005)
Plant copper/topaquinone-containing amine oxidases (CAOs, EC 1.4.3.6) are enzymes oxidising various amines. Here we report a study on the reactions of CAOs from grass pea (Lathyrus sativus), lentil (Lens esculenta) and Euphorbia characias, a Mediterranean shrub, with N6-aminoalkyl adenines representing combined analogues of cytokinins and polyamines. The following compounds were synthesised: N6-(3-aminopropyl)adenine, N6-(4-aminobutyl)adenine, N6-(4-amino-trans-but-2-enyl) adenine, N6-(4-amino-cis-but-2-enyl) adenine and N6-(4-aminobut-2-ynyl) adenine. From these, N6-(4-aminobutyl) adenine and N6-(4-amino-trans-but-2-enyl)adenine were found to be substrates for all three enzymes (Km approximately 10(-4)M). Absorption spectroscopy demonstrated such an interaction with the cofactor topaquinone, which is typical for common diamine substrates. However, only the former compound provided a regular reaction stoichiometry. Anaerobic absorption spectra of N6-(3-aminopropyl)adenine, N6-(4-amino-cis-but-2-enyl)adenine and N6-(4-aminobut-2-ynyl)adenine reactions revealed a similar kind of initial interaction, although the compounds finally inhibited the enzymes. Kinetic measurements allowed the determination of both inhibition type and strength; N6-(3-aminopropyl)adenine and N6-(4-amino-cis-but-2-enyl)adenine produced reversible inhibition (Ki approximately 10(-5) - 10(-4) M) whereas, N6-(4-aminobut-2-ynyl)adenine could be considered a powerful inactivator.
Keywords: Dihydroxyphenylalanine; koncentrace vodíkových iontů; Plants, Medicinal; Amine Oxidase (Copper-Containing); dihydroxyfenylalanin; Hydrogen-Ion Concentration; čočka; Temperature; Pisum sativum; spektrofotometrie; Cytokinins; cytokininy; teplota; léčivé rostliny; Substrate Specificity; chemické modely; Enzyme Inhibitors; substrátová specifita; adenin; rostlinné extrakty; Adenine; Plants; hrách setý; inhibitory enzymů; histaminasa; Plant Extracts; Kinetics; kinetika; Lens Plant; Models, Chemical; Spectrophotometry; rostliny